Peningkatan Pengetahuan dan Keterampilan Masyarakat Melalui Pembibitan Jamur Merang Di Desa Pasirukeum Kabupaten Karawang - Suhaeni Suhaeni; I Ketut Manu Mahatmayana; Indrajit Wicaksana; Yuyun Umaidah (BERNAS: Jurnal Pengabdian Kepada Masyarakat, 2023)
Straw mushrooms are one of the food ingredients that contain lots of nutrients and are liked by the community. One of the villages that became the center of straw mushrooms in Karawang Regency is Pasirukeum Village. The mushroom in this village was developed by farmers who are members of the Sri Muncul farmer group. However, over time, the production of straw mushrooms are decreasing year by year. One of the contributing factors is the low quality of mushroom seeds and the lack of knowledge and skills of farmers in conducting nurseries. Based on these problems, this community service activity aims to help the community provide solutions, namely in the form of socialization and training in nursery of straw mushroom . The method used is counseling and training on seed production of straw mushroom. There are four indicators used to measure farmers' knowledge, which are related to seeding and cultivation, mushroom quality, farming risk and income. The results of the implementation show that the knowledge of farmers (partners) about breeding and cultivation has increased by 27%, farmers' knowledge regarding the quality of straw mushrooms has increased by 22.1%, increased knowledge of farmers related to farming risks has increased by 25.6% and increased knowledge of farmers related to income in farming. increased by 23.7%. The average increase in knowledge and skills of farmers as a whole is 24.6%.